2007
DOI: 10.2478/s11536-007-0027-1
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoacute abdomen in female caused by haematometrocolpos and haematosalpinx because hymen imperforatus: diagnosis and therapy of imperforate hymen

Abstract: AbstractWe present a case of atresia hymenalis in a 12.5 year old female who was admitted to gynecological emergency with a history of severe lower abdominal pains over the course of a few months. Provided are clinical pictures of the “Pseudoacute abdomen”. Upon clinical examination, we found blue, shiny, bulging and imperforated hymen. An abdominal mass was palpated in the vicinity of the navel. Transabdominal ultrasound demonstrated mass filled with thick liquid. “Mercedes hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…[3] Ultrasonography and MRI revealed grade hydronephrosis with hematocolpos that was causing marked distension of the uterus and cervix. [4] The diagnosis of imperforate hymen was made under sedation during instrumentation for the procedure by inspection of the protuberant mass on retraction of the labia. The patient was taken into operating room and a simple cruciate incision was made on the hymen under general anaesthesia which resulted in drainage of 500ml of yellowish non bloody mucosal secretion from vagina.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Ultrasonography and MRI revealed grade hydronephrosis with hematocolpos that was causing marked distension of the uterus and cervix. [4] The diagnosis of imperforate hymen was made under sedation during instrumentation for the procedure by inspection of the protuberant mass on retraction of the labia. The patient was taken into operating room and a simple cruciate incision was made on the hymen under general anaesthesia which resulted in drainage of 500ml of yellowish non bloody mucosal secretion from vagina.…”
Section: Resultsmentioning
confidence: 99%
“…Meraa Erna Vlahovic had reported a case of 12.5 years old girl who presented to the gynae emergency with pseudoacute abdomen with an abdominal mass and on examination was found to have slight bulging imperforate hymen and was treated with Mercedes hymenal incision and 1.2L of dark thick blood was drained out. [4] Obi O Ansiem reported a case of acute urinary retention secondary to imperforate hymen in a 14 years old Nigerian girl which was treated by a cruciate incision on the hymen. [5] Aslude et al have also reported two cases of hematocolpos in adolescent girls due to imperforate hymen.…”
Section: Resultsmentioning
confidence: 99%
“…However, the diagnosis of varicocele and even presence of abnormalities in semen cells is not necessarily equal to a diagnosis of sterility. Epidemiologic data show that the rate of males suffering from varicocele reaches 15% [15], but the percentage of male patients with fertility disturbances reaches only 5% of the whole male population. It has been estimated that sterility concerns about 20.0% of patients with varicocele [1].…”
mentioning
confidence: 99%